Metabolic reprogramming through mitochondrial biogenesis drives adenosine anti-inflammatory effects: new mechanism controlling gingival fibroblast hyper-inflammatory state - Paladines, Nathalie; Dawson, Shantiece; Ryan, Weston; Serrano-Lopez, Rogelio; Messer, Regina; Huo, Yuqing; Cutler, Christopher W.; Ramos-Junior, Erivan S.; Morandini, Ana Carolina (Frontiers in Immunology, 2023)
Fibroblasts are the dominant stromal cells in the gingival lamina propria with a well-established relevance in regulation of inflammation, and in innate immunity. This is exemplified by their hypersecretion of CXCL8, enhancing leukocyte infiltration in chronic and sustained inflammatory conditions. We have previously shown adenosine to be a key metabolic nucleoside that regulates stromal inflammation, but the underlying mechanisms linking adenosine to the metabolic status of fibroblasts and to the resultant inflammatory response are unclear. This study examined, by seahorse real-time cell metabolic analysis, the bioenergetics of the stromal fibroblast response to extracellular adenosine and IL-1β, focusing on CXCL8 secretion by primary human gingival fibroblasts (HGF). Markers of the glycolytic pathway and mitochondrial biogenesis were tracked through immunoblot. Further, the influence of adenosine on mitochondrial accumulation was measured by uptake of MitoTracker Red fluorescent probe and assessment of the role of FCCP (a mitochondrial uncoupler) in CXCL8 secretion and mitochondrial accumulation. Our results show that the anti-inflammatory response of HGF to extracellular adenosine, typified by reduced CXCL8 secretion, is mediated by mitochondrial oxidative phosphorylation, reflected in higher oxygen consumption rate (OCR). In the presence of IL-1β, adenosine-treated cells induced higher ATP production, basal respiration and proton leak compared to IL-1β without adenosine. Surprisingly, adenosine had no additional effect on the IL-1β-induced higher glycolysis rate demonstrated by the extracellular acidification rate (ECAR). In addition, the higher OCR in adenosine-stimulated cells was not due to the mitochondrial fuel dependency or capacity, but due to an increase in mitochondrial biogenesis and accumulation in the cells with concomitant decrease in mitophagy-required p-PINK1 marker. We detected the accumulation of functional mitochondria with increased activation of the AMPK/SIRT1/PGC-1α pathway. The adenosine-induced uptake of MitoTracker was abrogated by PGC-1α inhibition with SR-12898. In addition, the adenosine effects on reduced CXCL8 were ablated by treatment with FCCP, a potent uncoupler of mitochondrial oxidative phosphorylation. Our findings reveal a key role for mitochondrial bioenergetics in regulation of CXCL8-mediated inflammation by HGF through the adenosine/AMPK/SIRT1/PGC-1α axis. Therapeutically targeting this pathway in gingival fibroblasts might be a promising future strategy to modulate stromal-mediated sustained hyper-inflammatory responses.